Incidence and risk of QTc interval prolongation among cancer patients treated with vandetanib: a systematic review and meta-analysis. - Jiajie Zang; Shunquan Wu; Lei Tang; Xudong Xu; Jie Bai; Caicui Ding; Yue Chang; Long Yue; Enming Kang; Jia He (PLoS ONE, 2012)
Vandetanib is a multikinase inhibitor that is under assessment for the treatment of various cancers. QTc interval prolongation is one of the major adverse effects of this drug, but the reported incidence varies substantially among clinical trials. We performed a systematic review and meta-analysis to obtain a better understanding in the risk of QTc interval prolongation among cancer patients administered vandetanib.Eligible studies were phase II and III prospective clinical trials that involved cancer patients who were prescribed vandetanib 300 mg/d and that included data on QTc interval prolongation. The overall incidence and risk of QTc interval prolongation were calculated using random-effects or fixed-effects models, depending on the heterogeneity of the included studies. Nine trials with 2,188 patients were included for the meta-analysis. The overall incidence of all-grade and high-grade QTc interval prolongation was 16.4% (95% CI, 8.1-30.4%) and 3.7% (8.1-30.4%), respectively, among non-thyroid cancer patients, and 18.0% (10.7-28.6%) and 12.0% (4.5-28.0%), respectively, among thyroid cancer patients. Patients with thyroid cancer who had longer treatment duration also had a higher incidence of high-grade events, with a relative risk of 3.24 (1.57-6.71), than patients who had non-thyroid cancer. Vandetanib was associated with a significantly increased risk of all-grade QTc interval prolongation with overall Peto odds ratios of 7.26 (4.36-12.09) and 5.70 (3.09-10.53) among patients with non-thyroid cancer and thyroid cancer, respectively, compared to the controls.Treatment with vandetanib is associated with a significant increase in the overall incidence and risk of QTc interval prolongation. Different cancer types and treatment durations may affect the risk of developing high-grade QTc interval prolongation.